Economic feasibility of recycling urban waste in the city of lisbon - pt - an analysis using the green-en application (Research, Society and Development, 2020)
This article aims to describe the operation and applicability of the VERDES-PT application for the city of Lisbon, capital of Portugal, and to show the values that are wasted annually by the city. The methodology used is from the VERDES – PT program, which shows the numbers through reverse logistics. With the generation of domestic solid waste increasing on an exponential scale, the public agencies responsible for the management of this waste have been adopting recycling as one of the ways to reuse urban waste, not only as a raw material, but also as a generator of jobs and income to classes with less educational background. As a result, the city of Lisbon has an annual potential of 146 million euros that could be returned to public coffers, if selective collection was adopted for 100% of its generation of urban waste. But, as will be seen in this article, the city loses 68 million euros a year for not adopting a waste management policy that takes full advantage of its generation.